2014
DOI: 10.1021/ic5010352
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Ultrafine Bimetallic Ni–Pt Nanoparticles Inside the Pores of Metal–Organic Frameworks as Efficient Catalysts for Dehydrogenation of Alkaline Solution of Hydrazine

Abstract: We report a facile liquid impregnation approach for immobilization of ultrafine bimetallic Ni-Pt nanoparticles (NPs) inside the pores of MIL-101. The methods of powder X-ray diffraction, N2 physisorption, X-ray photoelectron spectroscopy, transmission electron microscopy, and inductively coupled plasma-atomic emission spectroscopy were employed to characterize the NiPt@MIL-101 catalysts and further indicated the as-synthesized Ni-Pt NPs were confined in the pores of MIL-101. These as-synthesized bimetallic NiP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 60 publications
(86 reference statements)
3
58
0
1
Order By: Relevance
“…The oxidized Ni cover on the surface was presumably formed during the sample preparation process for the XPS measurements, as reported before [12,30]. The Pt 4f 7/2 and Pt 4f 5/2 with BE of 70.6 and 73.9 eV correspond to metallic Pt (Fig.…”
Section: Catalyst Characterizationsupporting
confidence: 57%
“…The oxidized Ni cover on the surface was presumably formed during the sample preparation process for the XPS measurements, as reported before [12,30]. The Pt 4f 7/2 and Pt 4f 5/2 with BE of 70.6 and 73.9 eV correspond to metallic Pt (Fig.…”
Section: Catalyst Characterizationsupporting
confidence: 57%
“…[1][2][3] High hydrogen content (8.0 wt%) and easy recharging make hydrazine a promising hydrogen carrier. [4][5][6] Furthermore, hydrazine is a liquid-phase material, which has the potential to take the advantage of the existing liquid-based distribution infrastructure. Transition metals are usually considered as the ideal candidates for hydrogen generation from hydrazine.…”
Section: Introductionmentioning
confidence: 99%
“…It could be seen that most of the Ni is the nickel (II) species, and the fractions of the nickel (II) species in all 0.2%Pd-x%Ni/SBA-15 catalysts were approximately 90%, and only a small fraction of Ni was nickel (0) for all samples regardless of the Ni loading amount. The presence of nickel oxide also indicated that there was an electron transfer between Pd and Ni; at the same time, the sample exposed to air would also lead to the formation of nickel oxide [47][48][49][50].…”
Section: Hydrogenation Of Cal To Hald Over Pd-ni/sba-15mentioning
confidence: 99%